2021
DOI: 10.15244/pjoes/132815
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Phosphorus Forms in Wuyi Rock Region and Its Effect on Tea Quality-Related Constituents in Tea Garden Soil

Abstract: Phosphorus is an essential element for life, an innate constituent of soil organic matter, and a major anthropogenic input to terrestrial ecosystems. This paper employed the sequential extraction method for phosphorus fraction to study the distribution of phosphorus in different region in Wuyishan. Hierarchical cluster and correlation were used for investigating the relationship between the phosphorus form and tea quality-related constituents in Zhengyan Rock Tea (ZYRT), Banyan Rock Tea (BYRT) and Zhou Rock Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, P also affects the decomposition and metabolism of minerals and metabolites in tea plants, thereby affecting the yield and quality of tea [12]. Under P deficiency, the concentrations of total polyphenols, flavonoids, total free amino acids, theanine, and aspartate in green tea decrease [12][13][14]. K can be used as an activator of various enzymes in tea plants, participating in the growth and development activities of tea plants, such as promoting photosynthesis, protein synthesis, and the transportation of photosynthate to shoots [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, P also affects the decomposition and metabolism of minerals and metabolites in tea plants, thereby affecting the yield and quality of tea [12]. Under P deficiency, the concentrations of total polyphenols, flavonoids, total free amino acids, theanine, and aspartate in green tea decrease [12][13][14]. K can be used as an activator of various enzymes in tea plants, participating in the growth and development activities of tea plants, such as promoting photosynthesis, protein synthesis, and the transportation of photosynthate to shoots [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, tea yield and quality were closely related to the environment and soil composition of the tea tree-growing region, and a high content of quality indexes in fresh tea leaves was more conducive to obtaining high-quality finished tea [7,9]. Ye et al concluded that the differences in tea yield and quality in different regions were mainly caused by differences in soil physiological and biochemical indexes, which showed that the higher the content of nutrient elements in the soil, the more conducive to the improvement of tea yield and quality [10]. Therefore, there is no clear conclusion as to the extent to which differences in planting environment and differences in tea tree variety affect the yield and quality of tea, especially Wuyi rock tea.…”
Section: Introductionmentioning
confidence: 99%